Initial use of supplementary oxygen for trauma patients: a systematic review - Trine Grodum Eskesen; Josefine Stokholm Baekgaard; Jacob Steinmetz; Lars S Rasmussen (BMJ Open)
Objective This systematic review aimed to identify and describe the evidence for supplementary oxygen for spontaneously breathing trauma patients, and for high (0.60–0.90) versus low (0.30–0.50) inspiratory oxygen fraction (FiO2) for intubated trauma patients in the initial phase of treatment.Methods Several databases were systematically searched in September 2017 for studies fulfilling the following criteria: trauma patients (Population); supplementary oxygen/high FiO2 (Intervention) versus no supplementary oxygen/low FiO2 (Control) for spontaneously breathing or intubated trauma patients, respectively, in the initial phase of treatment; mortality, complications, days on mechanical ventilation and/or length of stay (LOS) in hospital/intensive care unit (ICU) (Outcomes); prospective interventional trials (Study design). Two independent reviewers screened and identified studies and extracted data from included studies.Results 6142 citations were screened with an inter-rater reliability (Cohen’s kappa) of 0.88. One interventional trial of intubated trauma patients was included. 68 trauma patients were randomised to receive an FiO2 of 0.80 (intervention group) or 0.50 (control group) during mechanical ventilation (first 6 hours). There was no significant difference in hospital or ICU LOS between the groups. No patient died in either group. Another interventional trial, not strictly fulfilling the inclusion criteria, was presented for descriptive purposes. 21 trauma patients were alternately assigned to two types of mechanical ventilation (first 48 hours), both aiming at an FiO2 of 0.40, but resulted in estimated mean FiO2s of 0.45 (intervention group) and 0.60 (control group). No difference in days on mechanical ventilation was found. Two patients in the control group died, none in the intervention group. No prospective, interventional trials on spontaneously breathing trauma patients were identified.Conclusions Evidence for the use of supplementary oxygen for spontaneously breathing trauma patients is lacking, and the evidence for low versus high FiO2 for intubated trauma patients is limited.PROSPERO registration number 42016050552